Representing Refugees in Children’s Transethnic Literature: Two Multilingual and Intermedial Narratives as a Case Study - Taronna, Annarita (Il Tolomeo)
This contribution aims to explore two picture books of transethnic literature that open up intermedial narrative paths by supporting each of the proposed books with a free accessible illustrated audio book. Accordingly, it examines the extent to which implementing English as a Foreign Language (EFL) lessons with such multimodal stories about migration can engage students in deconstructing such tropes as the idea of a national literature, a mother tongue language, a stable community of belonging and a hostile country of arrival that typically characterise mainstream migration narratives and paradigms.